2013
DOI: 10.1371/journal.pone.0070106
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 Levels do not Affect the Shell Structure of the Bivalve Arctica islandica from the Western Baltic

Abstract: Shells of the bivalve Arctica islandica are used to reconstruct paleo-environmental conditions (e.g. temperature) via biogeochemical proxies, i.e. biogenic components that are related closely to environmental parameters at the time of shell formation. Several studies have shown that proxies like element and isotope-ratios can be affected by shell growth and microstructure. Thus it is essential to evaluate the impact of changing environmental parameters such as high pCO2 and consequent changes in carbonate chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Berge et al, 2006;McClintock et al, 2009;Beniash et al, 2010;Parker et al, 2010;Melzner et al, 2011;Talmage and Gobler, 2011;Amaral et al, 2012;Hiebenthal et al, 2013;Coleman et al, 2014;Gobler et al, 2014;Milano et al, 2016), cold-water scleractinian corals (e.g. Form and Riebesell, 2011;McCulloch et al, 2012;Jantzen et al, 2013b;Büscher et al, 2017) and sea urchins (Suckling et al, 2015) (Table S1). The results of these studies show that, in general, seawater acidification reduces the growth rate of marine calcifiers (Michaelidis et al, 2005;Shirayama and Thornton, 2005;Berge et al, 2006;Bibby et al, 2007;Beniash et al, 2010;Nienhuis et al, 2010;Figure 11.…”
Section: Low Ph and Brachiopod Microstructurementioning
confidence: 99%
“…Berge et al, 2006;McClintock et al, 2009;Beniash et al, 2010;Parker et al, 2010;Melzner et al, 2011;Talmage and Gobler, 2011;Amaral et al, 2012;Hiebenthal et al, 2013;Coleman et al, 2014;Gobler et al, 2014;Milano et al, 2016), cold-water scleractinian corals (e.g. Form and Riebesell, 2011;McCulloch et al, 2012;Jantzen et al, 2013b;Büscher et al, 2017) and sea urchins (Suckling et al, 2015) (Table S1). The results of these studies show that, in general, seawater acidification reduces the growth rate of marine calcifiers (Michaelidis et al, 2005;Shirayama and Thornton, 2005;Berge et al, 2006;Bibby et al, 2007;Beniash et al, 2010;Nienhuis et al, 2010;Figure 11.…”
Section: Low Ph and Brachiopod Microstructurementioning
confidence: 99%
“…Consequently, the pH values of the EPF are below that of ambient seawater for most of the time, and the fluid is undersaturated with respect to CaCO 3 (Crenshaw 1972a, Heinemann et al 2012. Some bivalves can even calcify at high rates under acidified conditions of the surrounding seawater with a saturation state of CaCO 3 < 0.5 , Stemmer et al 2013. The microenvironment in which calcification occurs has to be highly supersaturated with respect to shell minerals.…”
Section: Introductionmentioning
confidence: 99%
“…The clam is a key species in Western Baltic benthic communities and flourishes in areas exposed to fluctuating environmental parameters as salinity, oxygen, and pCO 2 (Hansen et al 1999). Stemmer et al (2013) showed that shell growth was unaffected under elevated CO 2 levels. The present study helps to clarify the role of the EPF in the calcification process within young specimen of the ocean quahog by directly measuring ion dynamics with high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In the Baltic Sea, several studies of CO 2 effects have been undertaken on the organism level of fish (Frommel et al, 2013), zooplankton (Pansch et al, 2012;Vehmaa et al, 2012), macrophytes (Pajusalu et al, 2013), benthic species (Hiebenthal et al, 2013;Stemmer et al, 2013), and filamentous cyanobacteria (Czerny et al, 2009;Eichner et al, 2014;Wannicke et al, 2012). Studies on the impacts of elevated CO 2 at the ecosystem level, however, have thus far been limited to Kiel Bight in the western Baltic Sea (Engel et al, 2014;Rossoll et al, 2013;Schulz and Riebesell, 2013), which may fundamentally differ from other parts of the Baltic Sea.…”
Section: Introductionmentioning
confidence: 99%